2015
DOI: 10.1111/zsc.12117
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny and the underestimated species diversity of the endemic white‐bellied rat (Rodentia: Muridae:Niviventer) in Southeast Asia and China

Abstract: Q. (2015). Molecular phylogeny and the underestimated species diversity of the endemic white-bellied rat (Rodentia: Muridae: Niviventer) in Southeast Asia and China. -Zoologica Scripta, 44, 475-494.The white-bellied rat, Niviventer, is a genus endemic to Southeast Asia and China. However, the interspecific phylogenetic relationships and species diversity of this genus remain poorly understood. In the present study, single and multi-locus analyses were performed. Phylogenetic reconstruction on Cytochrome b (512… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 65 publications
3
29
0
Order By: Relevance
“… a : The topotype of N. ling was sequenced in Lu et al (2015) [14] and was included in the present study. Sample locality is not shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… a : The topotype of N. ling was sequenced in Lu et al (2015) [14] and was included in the present study. Sample locality is not shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular phylogenetic studies further found that the widely distributed species were paraphyletic or even polyphyletic (e.g., N. andersoni, N. confucianus, N. excelsior, and N. fulvescens ) [13]. Despite the possibility of misidentification, the number of putative species always exceeded that of recognized species [13, 14], implying that species diversity was underestimated. Thus, it was reasonable to re-evaluate the large body of remaining subspecies/synonyms within this genus.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations